Persepsi Pasien Terminal Terhadap Dukungan Spiritual Sebagai Bagian Dari Asuhan Keperawatan Paliative - Shindy Shindy; Iswadi Iswadi; Matda Yunartha (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Terminal patients treated in the Intensive Care Unit (ICU) often experience physical, psychological, social, and spiritual distress due to life-threatening conditions. Spiritual support is considered an important component of holistic nursing care that can help patients achieve peace, acceptance, and emotional comfort during end-of-life care. This study aimed to explore terminal patients’ perceptions of spiritual support as part of nursing care in the ICU at Royal Prima Hospital Jambi. This research used a qualitative method with a phenomenological approach. Participants were selected using purposive sampling techniques, involving seven terminal patients who met the inclusion criteria. Data were collected through in-depth semi-structured interviews and analyzed using Reflexive Thematic Analysis. The findings identified four main themes: experiences of crisis and uncertainty in ICU care, spirituality as a coping mechanism, nurses’ spiritual support as part of holistic nursing and positive perceptions of spiritual support in improving acceptance and emotional calmness. Participants perceived spiritual support through empathetic communication, emotional attention and facilitation of worship activities. Spiritual support provided by nurses contributed patients’ emotional stability, peace of mind and acceptance of their terminal condition. The study concludes that spiritual support is an essential aspect of holistic nursing care for terminal patients in ICU settings.